Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Pemahaman Konsep Matematika Siswa - Maisi Oktavia; Aniswita Aniswita; Ulva Rahmi; Tasnim Rahmat (Pusat riset dan Inovasi Nasional, 2024)
This study was motivated by the low understanding of mathematical concepts of class VIII students of SMP Negeri 4 Bukittinggi. Based on the results of the documentation study, the percentage of students with daily test scores below the 55 criterion ranged from 50% to 81%. Observations and interviews revealed that learning was still dominated by teachers, while students were less active in the learning process. This study aims to determine the significant effect of the Numbered Head Together (NHT) cooperative learning model on students' understanding of mathematical concepts. This experimental study used the Static Group Comparison Design. The population of the study was class VIII students of SMP Negeri 4 Bukittinggi in the 2021/2022 academic year consisting of 127 students from 4 classes. The sample was taken randomly, with class VIII1 as the experimental class and VIII2 as the control class. The research instrument was a mathematical concept understanding test. The results of data analysis using the t-test showed a calculated t value > t table (3.269 > 1.67) at a significance level of 0.05. From SPSS, a significant value of 0.02 <0.05 was obtained so that H0 was rejected and H1 was accepted. In conclusion, there is a significant influence of the NHT learning model on the understanding of mathematical concepts of class VIII students of SMP Negeri 4 Bukittinggi.